The Effect of Public Financial Reforms on Service Delivery in Uganda’s Local Government: A Case Study of Manafwa District Local Government - Lumera Damscuss (Uganda Christian University, 2024)
This study investigates the impact of public sector financial reforms on the efficiency and effectiveness of local government operations in Manafwa District, Uganda. Spanning five chapters, the research provides a comprehensive analysis of the reforms' influence on financial management practices within the district. Chapter One introduces the research background, highlighting the necessity of financial reforms in Uganda’s public sector due to challenges in governance and resource management. It establishes the study's objectives, which include assessing the reforms' impact on budget management, accountability, and service delivery in Manafwa District. Chapter Two reviews relevant literature, examining global and regional experiences with public sector financial reforms. It focuses on theoretical frameworks and empirical studies to contextualize the Ugandan reforms, emphasizing the role of institutional capacity and financial transparency. Chapter Three describes the research methodology, detailing the qualitative and quantitative methods used to gather data. This includes surveys, interviews with key stakeholders, and financial data analysis to evaluate the reforms' outcomes in Manafwa District. Chapter Four presents the findings, revealing how the reforms have influenced financial practices in the district. It discusses improvements in budgetary controls, increased accountability, and enhanced financial reporting, while also identifying ongoing challenges such as resource constraints and administrative inefficiencies. Chapter Five concludes with a discussion of the reforms’ overall impact, offering policy recommendations for further improvements. It suggests strategies to address identified challenges and enhance the effectiveness of financial management in Manafwa District and similar local government areas in Uganda.